2022
DOI: 10.1055/a-1901-9569
|View full text |Cite
|
Sign up to set email alerts
|

„Hyposplenie“, eine weitgehend unerkannte Immunschwäche: Ist die Sonografie hilfreich?

Abstract: ZusammenfassungDas Immundefizienzsyndrom der funktionellen Hyposplenie/Asplenie ist weitgehend unerkannt. Die Goldstandardprozedur stellt die Technetium-99m-Szintigrafie von hitzedenaturierten Erythrozyten (TSZ) sowie der Nachweis von pitted Erythrozyten oder Howell-Jolly-Körperchen (HJB) dar. Erste Arbeiten weisen darauf hin, dass dieses Krankheitsbild mit einer kleinen Milz assoziiert ist. Ziel der vorliegenden Übersicht ist es, den Stellenwert der B-Bild-Sonografie und der kont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It is noteworthy that the morphological study also revealed a reduction in the percentage of red pulp in most splenic nodules. According to literature data (9,10), the presence of Howell-Jolly bodies in peripheral blood smears is considered a reliable marker of hyposplenism. Occasional variations in the shape or size of erythrocytes in peripheral blood may be considered normal, but the presence of erythrocytes with inclusions indicates significant changes in the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the morphological study also revealed a reduction in the percentage of red pulp in most splenic nodules. According to literature data (9,10), the presence of Howell-Jolly bodies in peripheral blood smears is considered a reliable marker of hyposplenism. Occasional variations in the shape or size of erythrocytes in peripheral blood may be considered normal, but the presence of erythrocytes with inclusions indicates significant changes in the spleen.…”
Section: Discussionmentioning
confidence: 99%